Pengenalan dan latihan soal tes TOEFL guna meningkatkan kemampuan bahasa inggris pada mahasiswa - Aria Mulyapradana; Ary Dwi Anjarini; Aria Elshifa; Hafiz Gulam; Winarsih Winarsih (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
This activity is carried out to provide solutions to problems faced by students in improving their English language skills to face rapid technological developments so that they can compete globally. Proficient mastery of English positively impacts them; this English proficiency can be measured through the TOEFL test. The TOEFL test is a scary scourge for everyone, especially students, so training activities related to the TOEFL test were created. The participants of this activity were 39 students in semester 6 of the ITSNU Pekalongan Office Administration study program. The methods of this activity are observation, lecture, practice, and evaluation. As a result of this activity, all participants were enthusiastic about participating in every material presented by the speaker and had experience in doing TOEFL test questions. It is hoped that after participating in this activity, participants can appear confident and master the TOEFL test questions and time management of problem work to obtain satisfactory results.